'I can't believe I didn't learn this in school': 'refusing secondly' as an anti-racist English education framework. Issue 2 (2nd April 2020) - Neville, Mary L.
ABSTRACT: This study examines the responses of pre-service teachers (PSTs) to the young adult novel All American Boys in light of their viewing the 2016 documentary 13 th . In this paper, I use anti-racist English education scholarship to discuss how these two texts helped PSTs 'refuse to start with secondly.' I examine how Adichie's concept of 'refusing secondly' within readings of literature both affords and constrains the anti-racist possibilities of literature teacher preparation courses. Using qualitative methodologies, I analysed student reflections, recorded class discussions, and co-constructed class documents. Students connected the historical and the contemporary in considerations of race and racism. They also implicated societal institutions before situating themselves within the continuing legacies of race and racism. These findings demonstrate the ways that 'refusing secondly' may offer space for PSTs and teacher educators to use literature to navigate the continuous and indeterminate process of becoming more anti-racist.